Nanoparticles: A Broad‐Spectrum ROS‐Eliminating Material for Prevention of Inflammation and Drug‐Induced Organ Toxicity (Adv. Sci. 10/2018). Issue 10 (17th October 2018) - Li, Lanlan; Guo, Jiawei; Wang, Yuquan; Xiong, Xiaoxing; Tao, Hui; Li, Jin; Jia, Yi; Hu, Houyuan; Zhang, Jianxiang
Abstract : Uncontrolled inflammation contributes to the pathogenesis of numerous diseases. Scavenging of reactive oxygen species (ROS) is promising for treatment of inflammatory diseases. To circumvent current limitations, in article number1800781, Jianxiang Zhang and co‐workers report a material with broad‐spectrum ROS‐eliminating capability. A nanotherapy derived from this bioactive material shows superior efficacies in different mouse models of inflammation and oxidative stress injury.